2014
DOI: 10.1089/aid.2014.0005
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Effects of Omega-3 Fatty Acids on Triglycerides and High-Density Lipoprotein Subprofiles in HIV-Infected Persons with Hypertriglyceridemia

Abstract: Hypertriglyceridemia and low high-density lipoprotein (HDL)-cholesterol (HDL-C) may contribute to a presumed accelerated risk for cardiovascular disease in HIV-infected individuals. We evaluated the effect of omega-3 fatty acid treatment on triglycerides, low-density lipoprotein (LDL)-C, HDL-C, and HDL subpopulations. Forty-one HIVseropositive subjects with hypertriglyceridemia ( ‡ 150 mg/dl) on active antiretroviral therapy were enrolled in this placebo-controlled, double-blind, randomized, crossover trial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…We observed no change in circulating total cholesterol concentration after EPA and DHA supplementation, which is consistent with previous omega-3 fatty acids trials including some that were conducted in HIV-infected populations [22, 23]. Although having no effect on total cholesterol, some fish oil intervention trials showed increased HDL and LDL particle size [24-26].…”
Section: Discussionsupporting
confidence: 90%
“…We observed no change in circulating total cholesterol concentration after EPA and DHA supplementation, which is consistent with previous omega-3 fatty acids trials including some that were conducted in HIV-infected populations [22, 23]. Although having no effect on total cholesterol, some fish oil intervention trials showed increased HDL and LDL particle size [24-26].…”
Section: Discussionsupporting
confidence: 90%
“…We found that in HIV-seropositive patients, this dose decreased triglycerides (TG) as has been previously reported in these patients [ 11 ]. Also Parandi et al [ 26 ] reported a decrease of 63.2 ± 86.9 mg/dl without change in total cholesterol, LDL-C, or HDL-C in 41 HIV+ subjects with hypertriglyceridemia (>150 mg/dl) after omega 3 fatty acid treatment (1.9 g EPA and 1.5 g DHA). However; Oliveira et al [ 27 ] found no effect on lipids after using 3 g fish oil in similar patients.…”
Section: Discussionmentioning
confidence: 99%
“…An additional three studies were excluded because they reported incomplete data. Finally, nine studies were eligible and included in the meta-analysis [12][13][14][15][16][17][18][19][20]. The study selection process is shown in Figure 1.…”
Section: Flow and Characteristics Of The Included Studiesmentioning
confidence: 99%